Program implementation of the Rating Methods of preference ranking - Torres, Kelly (2005)
Tide charts, based upon harmonic analysis, is the general method of choice for predicting water levels. In the shallow waters of the Gulf of Mexico, however, tide charts are woefully inadequate for the prediction of water levels. We have developed a number of models for the prediction of water levels. In this paper we summarize these methods and discuss the development of an axiomatic tool that we use to measure the quality of predictions of water levels in the estuaries and shallow waters of the Gulf of Mexico. This quality measure is based upon the preference rankings of National Ocean Service criteria by experts in the field.